2015
DOI: 10.1007/s00216-015-9007-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of fuzzy chromatography mass spectrometric (FCMS) fingerprinting and chemometric analysis for differentiation of whole-grain and refined wheat (T. aestivum) flour

Abstract: A fuzzy chromatography mass spectrometric (FCMS) fingerprinting method combined with chemometric analysis has been established for rapid discrimination of whole-grain flour (WF) from refined wheat flour (RF). Bran, germ, endosperm, and WF from three local cultivars or purchased from a grocery store were studied. The state of refinement (whole vs. refined) of wheat flour was differentiated successfully by use of principal-components analysis (PCA) and soft independent modeling of class analogy (SIMCA), despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…Thus simple principal component analysis of the NIR spectral data showed significant potential for analysis refined and whole wheat processed product prepared from different wheat cultivars. Similar separation of whole and refined wheat samples was recently reported by Geng et al (2015) using fuzzy chromatography mass chromatographic using multivariate analysis tools namely, PCA and SIMCA. In addition, Fig.…”
Section: Nir and Uv Spectral Fingerprintssupporting
confidence: 76%
See 1 more Smart Citation
“…Thus simple principal component analysis of the NIR spectral data showed significant potential for analysis refined and whole wheat processed product prepared from different wheat cultivars. Similar separation of whole and refined wheat samples was recently reported by Geng et al (2015) using fuzzy chromatography mass chromatographic using multivariate analysis tools namely, PCA and SIMCA. In addition, Fig.…”
Section: Nir and Uv Spectral Fingerprintssupporting
confidence: 76%
“…There are large number of studies showing the phytochemical content of whole grain is significantly higher as compared to the refined grain. Recently, Geng et al (2015) showed the application of fuzzy chromatography mass chromatographic followed by chemometrics analysis (principal component analysis (PCA) and soft independent modeling of class analogy (SIMCA)) protocols for differentiation of whole and refined grains.…”
Section: Introductionmentioning
confidence: 99%
“…No special effort was dedicated to the study of C ‐glycosyl flavonoids of wheat germ. Our previous work has shown that apigenin 6‐ C ‐pentosyl‐8‐ C ‐hexoside and its isomers from the germ fraction are the prominent discriminatory compounds to differentiate between whole grain and refined wheat flour . Asenstorfer et al also reported that apigenin C ‐diglycosides which are responsible for the yellow color of alkaline noodle are located only in the germ of wheat grains .…”
Section: Introductionmentioning
confidence: 64%
“…Our previous work has shown that apigenin 6-C-pentosyl-8-C-hexoside and its isomers from the germ fraction are the prominent discriminatory compounds to differentiate between whole grain and refined wheat flour. [22] Asenstorfer et al also reported that apigenin C-diglycosides which are responsible for the yellow color of alkaline noodle are located only in the germ of wheat grains. [23] Hence, in the current study, closer attention was paid to wheat germ regarding its flavonoid constituents owing to their nutritional value and biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…The dried tubers were ground into powder and then passed through a 20-mesh sieve for uniform size distribution. The samples were processed as described previously with minor modifications [35,36]. Briefly, a 100 mg aliquot of each sample was extracted with 5.0 mL of methanol-water (7 : 3, v/v) using a sonicator (Advanced Sonic Processing Systems) at 16 kHz with 300 W power for 35 min, and then centrifuged at 13 000 g for 15 min in a Contifuge 28RS centrifuge (Heraeus) at 4°C.…”
Section: Sample Preparationmentioning
confidence: 99%